From Clay Tablets to Digital Reformation: A Review on Knowledge Preservation Practices - Monisikha Borgohain; Dipen Deka (Record and Library Journal, 2026)
Background of the study: Knowledge preservation has evolved from ancient physical mediums (clay tablets, papyrus) to digital formats. Modern practices address media degradation, format obsolescence, and the integration of Artificial Intelligence (AI) into knowledge resource management. Purpose: This paper reviews preservation development from ancient Mesopotamia to contemporary AI to understand how technological advancements safeguard documentary heritage. Method: An extensive literature review of 450 peer-reviewed articles, e-books, and reports was conducted. Applying strict inclusion criteria yielded 350 English-language works for full-text analysis across five chronological themes. Findings: The study identifies five distinct phases: early preservation (clay tablets to codices), medieval monastic copying, the print era, public accessibility, and the digital transition. Key milestones include the 1439 printing press, 1928 magnetic tape, 2006 cloud storage, and modern AI-driven metadata and predictive analytics. Conclusion: Preservation practices have evolved through successive technological, institutional, and societal changes that have influenced how knowledge is organized, protected, and accessed. Historical and contemporary evidence suggests that sustainable preservation depends not only on technological solutions but also on strong governance and organizational capacity. Addressing future preservation challenges will require more coordination that combine technical innovation with ethical and cultural considerations.